The distributional effects of public education in Greece in the era of depression - Koutsampelas, Christos; Andreou, Sofia N.; Tsakloglou, Panos (My University, 2015)
This paper examines the distributional effects of publicly provided education services in Greece during the tumultuous period of 2009-2013; that is before the crisis erupted and at its peak. We adopt two approaches in estimating the monetary value of public education transfers. The ‘objective’ distributional effects of public education are measured through static incidence analysis under the assumption that the value of public transfers to the beneficiaries is equal to the average cost of producing the corresponding public services. The ‘perceived’ distributional effects of public education are measured via demand analysis through which we derive a money metric of households’ willingness to pay for public education. The juxtaposition of the two approaches yields empirical results which are valuable to policy makers.
Keywords: Public education; Income distribution; Demand analysis